2018
DOI: 10.1242/jcs.211904
|View full text |Cite
|
Sign up to set email alerts
|

SUMO-specific proteases and isopeptidases of the SENP family at a glance

Abstract: The ubiquitin-related SUMO system controls many cellular signaling networks. In mammalian cells, three SUMO forms (SUMO1, SUMO2 and SUMO3) act as covalent modifiers of up to thousands of cellular proteins. SUMO conjugation affects cell function mainly by regulating the plasticity of protein networks. Importantly, the modification is reversible and highly dynamic. Cysteine proteases of the sentrin-specific protease (SENP) family reverse SUMO conjugation in mammalian cells. In this Cell Science at a Glance artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
151
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(168 citation statements)
references
References 99 publications
2
151
0
Order By: Relevance
“…SUMO proteins are highly conserved through evolution and the human genome encodes four SUMO genes, of which three genes (SUMO1, SUMO2, and SUMO3) are ubiquitously expressed in all cells 1,2 . Prior to conjugation, the immature SUMO proteins are C-terminally processed by sentrin-specific proteases 3 . These proteases also cleave the isopeptide bond formed between the ε-amino group of the acceptor lysine residues and the C-terminus residue of the conjugated SUMO proteins.…”
mentioning
confidence: 99%
“…SUMO proteins are highly conserved through evolution and the human genome encodes four SUMO genes, of which three genes (SUMO1, SUMO2, and SUMO3) are ubiquitously expressed in all cells 1,2 . Prior to conjugation, the immature SUMO proteins are C-terminally processed by sentrin-specific proteases 3 . These proteases also cleave the isopeptide bond formed between the ε-amino group of the acceptor lysine residues and the C-terminus residue of the conjugated SUMO proteins.…”
mentioning
confidence: 99%
“…The ability of Exendin 4 and DPPIV inhibitor to increase insulin secretion (and improve glucose tolerance) appears to depend on the expression of SENP1 within β‐cells, as indicated both by the inability of Exendin 4 to enhance β‐cell exocytosis in the βSENP1 −/− cells and the inability of the MK‐0626 DPPIV inhibitor to increase plasma insulin acutely and improve glucose tolerance in either the βSENP1 +/− or the βSENP1 − / − mice. SENP1 is an isopeptidase that selectively cleaves SUMO peptides from their target proteins (Kunz, Piller, and Müller, 2018). SENP1 is redox‐sensitive (Xu et al, 2008) and within β‐cells appears to be activated downstream of the glucose‐induced mitochondrial export of (iso)citrate (Ferdaoussi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SENPs display SUMO paralog specificity and thus serve as critical determinants of SUMO pathways. Detailed review on SENPs can be found elsewhere [68,69,70].…”
Section: The Sumo Pathway and The Cellular Sumo Landscapementioning
confidence: 99%